Corn grain yield and plant characteristics in two water environments - Frank, Brian James (Kansas State University, 2010)
Corn (Zea mays L.) yields are often reduced by limited pumping capacity of irrigation wells drawing from the High Plains Aquifer. As a result of decreased well capacities in this region, many irrigation systems no longer have the ability to meet peak irrigation (water) needs during the growing season. The purpose of this study was to measure easily identifiable plant characteristics of corn hybrids and relate those characteristics with the ability to maintain yield under water-limited conditions. This study involved measuring several plant characteristics of 18 corn hybrids grown under irrigated and dryland conditions near Tribune, KS during the growing seasons of 2005, 2006, and 2007. During each year, hot and dry conditions occurred during silking which resulted in large differences, and many poor yields, in the dryland plots. The number of days and growing degree days (GDD) to initiation of silking were the variables most strongly correlated with grain yield in the dryland environment. The shorter the time it took to reach initiation of silking the greater the grain yield. The number of days, or the GDD, to initiation of silking in irrigated environments did not have a significant correlation with corn grain yield. Other characteristics including canopy temperature, PAR (photosynthetically active radiation), color, leaf angle, number of internodes, number of leaves, and leaf N had no significant correlation with corn grain yield for either dryland or irrigated environments in 2005 and 2006. In this study using hybrids with maturity ratings between 98 and 118 d, there were no significant differences in grain yield in the irrigated environment. In the dryland environment, the hybrids used (98 – 118 d) in this study resulted in a decrease in grain yield with an increase in maturity. By considering the maturity of a hybrid, a producer will potentially be able to better select a variety that will perform well in a growing season with potential or likely severe water cutbacks as a result of limited water supply or reduced well capacity.
Keywords: corn; drought; irrigated; physiology; morphology; plant characteristics; Agriculture, Agronomy (0285)